Awareness of Malaysian contractor in practicing waste recycling / Noor Anis Adila Azman - Azman, Noor Anis Adila (Faculty of Architecture, Planning and Surveying, 2015)
Reduce, reuse and recycle is a concept that people everywhere are starting to understand and apply in daily life. Product and little new material to be produced, saving raw materials and reducing energy consumption is the true definition of waste recycling. There are many advantages can get from recycling activity, for example by using a resource that would otherwise be wasted. Practice recycling can reduce or prevent the amount of waste going to landfill. Besides, it can reduce the costs involved in the disposal of waste, which ultimately leads savings for the community. By practicing recycled, can reduce pollution and at the same time protect natural resources. The aim is to investigate the factors that can enhance recycling practice among Malaysian contractor. The objectives are to indicate the awareness of Malaysian Contractors in practicing waste recycling on the construction site. To determine the significant factors that hinder Malaysian contractors from practicing waste recycling. To recommend initiatives for encouraging Malaysian contractor to practice waste recycling. Using simple random sampling technique, a survey was conducted by distributing questionnaires to 30 respondents in order to obtain required data. Microsoft excel was used to analyze the data obtained. The study concludes that their reused method is very suitable to manage the waste.